A estratégia como prática social : um estudo sobre a relação das práticas sociais dos gestores no "fazer estratégia" em uma empresa familiar - Venturini, Fabiano Ewald (2014)
This work aims to understand the "strategizing" within a family business from the social practices surrounding their managers. Social practices are conceived as a social phenomenon, which is born and develops the interaction and relationship between indiv